Training law enforcement to respond to opioid overdose with naloxone: Impact on knowledge, attitudes, and interactions with community members. (1st August 2016) - Wagner, Karla D.; Bovet, L. James; Haynes, Bruce; Joshua, Alfred; Davidson, Peter J.
Highlights: Law enforcement officers are being trained to respond to opioid overdoses with naloxone. Brief trainings can improve competency and confidence in overdose response. Improved community relations could impact willingness to call 911 for overdose victims. Abstract: Background: Training law enforcement officers (LEOs) to administer naloxone to opioid overdose victims is increasingly part of comprehensive efforts to reduce opioid overdose deaths. Such efforts could yield positive interactions between LEOs and community members and might ultimately help lower overdose death rates. Methods: We evaluated a pilot LEO naloxone program by (1) assessing opioid overdose knowledge and attitudes (competency in responding, concerns about naloxone administration, and attitudes towards overdose victims) before and after a 30 min training on overdose and naloxone administration, and (2) conducting qualitative interviews with LEOs who used naloxone to respond to overdose emergencies after the training. Results: Eighty-one LEOs provided pre- and post-training data. Nearly all (89%) had responded to an overdose while serving as an LEO. Statistically significant increases were observed in nearly all items measuring opioid overdose knowledge (p's = 0.04 to <0.0001). Opioid overdose competencies (p < 0.001) and concerns about naloxone administration (p < 0.001) significantly improved after the training, while there was no change in attitudes towards overdose victims (p = 0.90). LEOs administered naloxone 11 times; nine victims survived and three of the nine surviving victims made at least one visit to substance abuse treatment as a result of a LEO-provided referral. Qualitative data suggest that LEOs had generally positive experiences when they employed the skills from the training. Conclusions: Training LEOs in naloxone administration can increase knowledge and confidence in managing opioid overdose emergencies. Perhaps most importantly, training LEOs to respond to opioid overdose emergencies may have positive effects for LEOs and overdose victims.